Comprehensive spectroscopic and computational insight into the binding of vanillin with human transferrin: targeting neuroinflammation in Alzheimer’s disease therapeutics - Alrouji, Mohammed; Yasmin, Sabina; Alhumaydhi, Fahad A.; Sharaf, Sharaf E.; Shahwan, Moyad; Furkan, Mohammad; Khan, Rizwan Hasan; Shamsi, Anas (Frontiers in Pharmacology, 2024)
In present times, vanillin stands out as a promising therapeutic molecule that can be implicated in the treatment of neurodegenerative disorders, notably Alzheimer's disease (AD). This can be attributed to the highly potent scavenging activity of vanillin against reactive oxygen species (ROS). Oxidative stress leads to generation of ROS that serves a critical role in AD's pathological progression. It is apparent from various studies that diets rich in polyphenols prevent oxidative stress associated with AD development, implying the crucial role of vanillin in AD therapeutics. It is crucial to maintain iron balance to manage AD associated oxidative stress, unveiling the significance of human transferrin (hTf) that maintains iron homeostasis.Here, we have performed an integrated study of spectroscopic and computational approaches to get insight into the binding mechanism of vanillin with hTf. In the preliminary study, Mmolecular docking deciphered that vanillin primarily occupies the hTf binding pocket, forming multiple interactions with its key residues. Moreover, the binding mechanism was evaluated at an atomistic level employing comprehensive molecular dynamic (MD) simulation. MD analysis demonstrated that binding of vanillin to hTf stabilizes its structure, without inducing any significant alterations in its native conformation. The docked complex was maintained throughout the simulations without changing its original conformation.Essential dynamics analysis further confirms that hTf achieved a stable conformation with vanillin. The outcomes were further supplemented by fluorescence spectroscopy which confirms the formation of stable hTf-vanillin complex. Taken together, Tthe current study unveils the interaction mechanism of vanillin with hTf, thereby and providing a platform to use vanillin in AD therapeutics in the context of iron homeostasis.